Raoultella ornithinolytica in MALT-type non-Hodgkin Lymphoma - Rui Seixas (SMC MEDIA SRL, 2021)
Raoultella ornithinolytica is a bacterium that belongs to the Enterobacteriaceae family. The most frequently reported infections are gastrointestinal and hepatobiliary. Urinary tract infections are very rarely reported and bloodstream infections are usually reported without an identified source. This bacterium is responsible for an increasing number of infections, especially in immunocompromised patients. The authors describe the first case ever reported of an immunocompromised patient due to non-Hodgkin lymphoma MALT type and corticotherapy, who developed urinary tract infection and subsequently bacteriemia due to this pathogen.